2016
DOI: 10.3389/fmicb.2016.00403
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of Cultivable Communities of Co-occurring Endophytes and Pathogens in Wheat

Abstract: The aim of this work was to investigate the diversity of endogenous microbes from wheat (Triticum aestivum) and to study the structure of its microbial communities, with the ultimate goal to provide candidate strains for future evaluation as potential biological control agents against wheat diseases. We sampled plants from two wheat cultivars, Apache and Caphorn, showing different levels of susceptibility to Fusarium head blight, a major disease of wheat, and tested for variation in microbial diversity and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 126 publications
(134 reference statements)
6
59
1
Order By: Relevance
“…Although roots were only sampled from A. variabilis, they yielded higher proportions of saprophytes than the aerial portions of the plants. Similar results were demonstrated for roots and aerial parts of wheat (Comby et al, 2016). David et al (2016) demonstrated that the influence of location and host species on fungal endophyte community composition also depended on plant part, in that environment and host species were very important in endophyte community composition from leaves of beach grasses, but only the sand dune environment was important for determining the endophyte community from roots.…”
Section: Sphaerophysa Salsula Oxytropis Glabra Astragalus Variabilissupporting
confidence: 71%
“…Although roots were only sampled from A. variabilis, they yielded higher proportions of saprophytes than the aerial portions of the plants. Similar results were demonstrated for roots and aerial parts of wheat (Comby et al, 2016). David et al (2016) demonstrated that the influence of location and host species on fungal endophyte community composition also depended on plant part, in that environment and host species were very important in endophyte community composition from leaves of beach grasses, but only the sand dune environment was important for determining the endophyte community from roots.…”
Section: Sphaerophysa Salsula Oxytropis Glabra Astragalus Variabilissupporting
confidence: 71%
“…), and the aerial tissues and roots of wheat (Comby et al. ) and other grasses (Sánchez Márquez et al. , ).…”
Section: Discussionmentioning
confidence: 99%
“…), in roots of wheat (Comby et al. ), and in leaves and roots of other grasses (Sánchez Márquez et al. , ); only recently, M. alpina was described as an entomopathogen (Edgington et al.…”
Section: Discussionmentioning
confidence: 99%
“…All plants in natural habitats are believed to harbour endophytes (Aly et al , 2011 ) and they can be tissue-type specifi c or systemic (Zabalgogeazcoa, 2008 ). Th e life cycles of the majority of endophytes are not completely understood, but it is clear that some endophytes do not remain exclusively within the plant throughout their whole life cycle, which means that they can potentially be latent pathogens (Comby et al , 2016 ) or latent saprotrophs , or can represent early colonisation by rhizobia or mycorrhizal fungi (Porras-Alfaro and Bayman, 2011 ). Th e diversity of diff erent available at https://www.cambridge.org/core/terms.…”
Section: Endophyte Host Range and The Targeted Search For Benefi Cialmentioning
confidence: 99%